PENGEMBANGAN BUKU AJAR PENDIDIKAN HUKUM - Siti Awaliyah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: In accordance withthe results of the preliminary study, there is aneedto compose an instructional book on law education for high school students. It needs to be done in order to widen the students, knowledge. The advanced study aims at developing the instructional book, and testing the levels of attractiveness, effectiveness, and effrciency of the book. Methods being used in thls developmental study are expert evaluation trial, small group trial, and big group trial' The product is evaluated by experts in iaW instructional media, and teaching and learning' Based on the recommendation of the experts, the researcher makes some improvements on the product' Afterwards, the small group triaiis conducted. The results showthatthe attractiveness level is 19oh;mean of the formative tests scores is 76,6; and the subjects need 18 minutes in average to accomplish everything per chapter. Further, the researcher conducts the big group trial' There is a betterment inthe results: the atffactiveness level is 79,2Vo: mean of the formative tests scores is 83; and the subjects need 20 minutes in average to accomplish everything per chapter'